Thomas Hobbes critical assessments - King, Preston T (Critical assessments of leading political philosophers, 1993)
This collection brings together the rich periodical literature on one of the greatest English philosophers. These definitive essays range across Hobbes' work in ethics, metaphysics, law, politics, history, science and religion.